Silicon Mitigates Manganese Deficiency Stress by Regulating the Physiology and Activity of Antioxidant Enzymes in Sorghum Plants - de Oliveira, Raimundo Leonardo Lima [UNESP]; de Mello Prado, Renato [UNESP]; Felisberto, Guilherme [UNESP]; Checchio, Mirela Vantini [UNESP]; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2019)
Silicon (Si) may mitigate different nutritional stresses in cultivated plants associated with a higher activity of enzymatic compounds, which act in the reduction of oxidative stress. Thus, this study aimed to evaluate the effects of Si supplied via root (nutrient solution) and leaf spraying to mitigate manganese (Mn) deficiency, considering the biochemical and physiological aspects of grain sorghum plants. The experiments were carried out in a greenhouse under a hydroponic system. Initially, a test was performed to evaluate the source and concentration of Si for leaf spraying of sorghum plants. Subsequently, the study was carried out with the following treatments: without Si, Si via leaf spraying, and Si via root on the omission and presence of Mn. Stabilized sodium and potassium silicate (SiNaKE) was applied in three leaf sprayings (1.0 g L−1 Si) and in the nutrient solution (2.0 mmol L−1 Si). Mn-deficient plants without Si presented higher concentrations of hydrogen peroxide (H2O2), malondialdehyde (MDA), and lower activity of superoxide dismutase (SOD), with reflections on the decrease of photosynthesis, leaf area, and shoot dry matter. Silicon mitigated the effects of stress due to Mn deficiency in sorghum plants, and the application via root of the beneficial element was more effective than leaf spraying. This benefit of Si was evidenced by the higher activity of superoxide dismutase, reducing oxidative stress, with reflections on photosynthesis, leaf area, manganese use efficiency, and dry matter production of plants.
Keywords: Beneficial element; Nutritional stress; Si sources; Sorghum bicolor L